The Focus on Youth Prevention and Education Research Programme - Deveaux, Lynette; Rolle, Glenda (International Journal of Bahamian Studies, 2016)
Like many developing or transitional countries affected by the HIV epidemic, The Bahamas has been deeply committed to HIV and sexually transmitted infection reduction and continues to make great strides in controlling the epidemic within its boundaries. Encouraged by the impact of the Focus on Youth Caribbean (FOYC), a school-based HIV/AIDS prevention programme and its parenting component on Grade 6 and Grade 10 students and their parents, a team of researchers from The Bahamas and the United States sought to implement a similar programme at a national level, while simultaneously evaluating factors that impact the sustainability of sexual risk-reduction programmes like FOYC. This paper describes five research projects conducted in The Bahamas between 1998 and 2016 and includes a list of over 40 published research articles